Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/j.2334-5837.2005.tb00742.x
|View full text |Cite
|
Sign up to set email alerts
|

8.3.1 Towards an Integrated Methodology for the Model‐based Development of Embedded Automotive Control Software

Abstract: The complexity of developing automotive control unit software can generally not be mastered without an efficient development methodology. The development discipline activities requirements, modelling / implementation and quality assurance are, for this reason, supported by individual methods. In order to optimally coordinate the methods with one another during their deployment, a structured integration of these individual specialised methods is, however, essential. The following paper, using the model‐based de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…On the other, it must be shown that the data-oriented tool integration is sufficient for the implementation of methods that work with artifacts from different tools. Last but not least, we have to integrate the introduced approaches into the global concept of an integrated methodology [32], of which they are fundamental parts and important steps towards realizing this vision.…”
Section: Resultsmentioning
confidence: 99%
“…On the other, it must be shown that the data-oriented tool integration is sufficient for the implementation of methods that work with artifacts from different tools. Last but not least, we have to integrate the introduced approaches into the global concept of an integrated methodology [32], of which they are fundamental parts and important steps towards realizing this vision.…”
Section: Resultsmentioning
confidence: 99%